Apatinib Combined With SOX Regimen in Conversion Treatment of Advanced Gastric Cancer: A Case Series and Literature Review - Jiang, Dingyi; Xu, Yunyun; Chen, Yunwang; Jiang, Jiahong; Wang, Mingxing; Yang, Min; Chen, Zheling; Yang, Liu (Frontiers in Pharmacology, 2020)
Gastric cancer is a common digestive tract tumor and the second most prevalent cancer. The prognosis of advanced gastric cancer is poor. Conversion therapy can reduce tumor burden, downgrade tumor, and increase the possibility of complete resection, thus prolonging the survival time of patients with gastric cancer. In conversion therapy, chemotherapy and targeted therapy are the main methods of medical treatment, which can control tumor growth and recurrence. As an antiangiogenic targeted drug, apatinib is widely used in the third-line treatment of advanced gastric cancer. Recent studies have shown that it may be of great help in rapid reduction of tumor stage and improvement of prognosis in conversion therapy. This study reported 3 cases of gastric cancer complicated with multiple abdominal and retroperitoneal lymph node metastases. After receiving apatinib combined with SOX regimen for 4 cycles, computed tomography showed that the focus and lymph node metastasis were reduced after treatment, and primary tumors were resected. Postoperative pathology result showed that the patients got R0 resection. After radical surgery, the maintenance therapy including apatinib was given. The progression-free survival time was more than 10 months. Apatinib combined with SOX regimen as a conversion therapy for advanced gastric adenocarcinoma increases the possibility of successful surgical resection and prolongs the survival time of patients.